Low profile microstrip fed printed antenna for portable RF energy harvesting system - Alladi, Rajasekhar; Naidu, Praveen V.; P, Raveendra; Kotha, Srinivasa Reddy; Charan, Siva; Harish, Sai (International Journal of Engineering and Technology, 2018)
This work presents, a printed wideband microstrip antenna that can be used for portable RF energy harvesting applications. The antenna is designed, simulated and validated using 3D electromagnetic HFSS simulator. The targeted frequency band of operations are from 0.825 GHz to 1.05 GHz for catering GSM/3G wireless applications. Following the antenna design in the HFSS software, the structure has been fabricated on low cost substrate FR4 and the structure performance is analyzed experimentally. The achieved wideband, omni directional patterns with constant gain monopole antenna can be suitable for all portable system applications.